2018
DOI: 10.1073/pnas.1812855115
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the evolution of wheat avenin-like proteins in wild emmer wheat ( Triticum dicoccoides )

Abstract: SignificanceWheat grain avenin-like proteins (ALPs) have functions for dough quality and antifungal activities. A genome-wide characterization of ALP encoding genes in bread wheat is conducted. Results showed that most ALPs are transcriptionally active in developing grains and are up-regulated upon Bgt infection. The allelic diversity of ALPs in 21 natural populations of wild emmer wheat (WEW) in Israel were studied. Many ALP allelic variations in WEW were associated with regional environmental adaption. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 46 publications
0
36
0
1
Order By: Relevance
“…Mutations or silencing of such genes are not lethal for the plant, so the evolutionary selection pressure on these genes is much lower than for functional genes [6] . As a result, these genes can accumulate more mutations, making them ideal model molecules for studying a range of biological fundamental processes [7][8][9][10] . It is worth noting that past work has been primarily focused on the applied aspects of using these proteins to increase wheat end product quality.…”
Section: Wheat Gluten Protein Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations or silencing of such genes are not lethal for the plant, so the evolutionary selection pressure on these genes is much lower than for functional genes [6] . As a result, these genes can accumulate more mutations, making them ideal model molecules for studying a range of biological fundamental processes [7][8][9][10] . It is worth noting that past work has been primarily focused on the applied aspects of using these proteins to increase wheat end product quality.…”
Section: Wheat Gluten Protein Variationsmentioning
confidence: 99%
“…Their value in theoretical research has been largely ignored. So far, only Zhang et al [8] has reported a biological function other than the storage function for gluten, an antifungal function of a newly identified special gluten protein, namely aveninlike protein, which is quite similar to the gliadins in structure. Until now, extensive studies have provided substantial information about the relationship between gluten structures and properties in relation to end product quality.…”
Section: Wheat Gluten Protein Variationsmentioning
confidence: 99%
“…Improvements in wheat DH production have resulted from co-culture with ovaries [11] and n-butanol treatment [12,13]. Approximately 90% of the DH lines developed in our program are destined for plant breeding companies, with the remaining populations used for research projects throughout Australia [14,15]. Genotype variability in key production parameters, such as embryo production, green plant regeneration and chromosome doubling, is an ongoing challenge, especially for the high-throughput production of breeding populations.…”
Section: Introductionmentioning
confidence: 99%
“…In wheat, the ALPs can be detected in the gluten-enriched fraction, including among others a range of gliadins, glutenins, protease inhibitors and LTPs [44]. The ALPs were named due to sequence homology with avenins of oats [45], most closely to avenin-3 [46], and α-, γ-gliadins [47]. Kasarda et al [48] characterized a novel ALP called farinin, composed by two disulphide-linked small polypeptides subsequent to a proteolytic cleavage of a precursor polypeptide at an Asn-Glu (N-E) peptide bond.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the study by Altenbach et al [55], the farinins (ALPs) comprised from 2.6 to 3.1% of the protein in the SDS-extractable polymeric proteins (EPP) and 1.9-2.4% of the protein in the SDS-unextractable polymeric proteins (UPP), and they were influenced by post-anthesis fertilizer. Both type b subunits (bx and by) of ALPs were reported to have non-functional pseudogenes in Brachypodium distachyon L accessions, Triticum dicoccoides, and T. aestivum [47,56]. Most recently, more novel alleles of ALP were found in Aegilops tauschii Coss.…”
Section: Introductionmentioning
confidence: 99%